La cosmovisión de Hildegarda de Bingen (Teología, 2018)
The title of Doctor of the Church, in the words of Cardinal Amato, Prefect of the Congregation for the Causes of Saints, is conferred on those who “with their eminent doctrine have contributed to the deepening of the knowledge of the divine Revelation, enrichening the theological heritage of the Church and fostering in the faithful the growth in faith and charity. This is, in brief, the meaning of the proclamation of doctor of the Church”. And Benedict XVI, declaring Saint Hildegard Doctor of the Church, says: “Hildegard’s teaching is considered eminent both for its depth, the correctness of its interpretation, and the originality of its views”. This article provides some theological, anthropological and ecclesial elements of the thought of the abbess of Bingen, which contribute to justify the title with which she was honored on the 7th October 2012.
Keywords: Hildegard of Bingen; Trinity; Creation; Man; Church